Post-migration Representations of Istanbul in Turkey’s Independent Cinema - Yigit, Zehra (European Journal of Multidisciplinary Studies, 2022)
This study aims to analyze the representation of Istanbul in the Independent Cinema of Turkey. My study focuses on Istanbul not only because Istanbul presents an opportunity for micro-scaled analysis for Turkey, but also because of the fact that the cinema of Turkey being Istanbul-oriented. I focus on the major political and sociological turning points of Turkey and how all these transformations have altered the presentation of Istanbul in the movies of the same period. The migration remained to be one of those main turning points in people’s life and their conditions - in particular migration from rural to urban - on which this study is focused.
Keywords: Istanbul, representation, Independent cinema of Turkey, social changes, migration.